The Customer’s Level of Satisfaction of Self- Ordering on Selected Fast Food Chain at District 1, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Self-service kiosks have significantly improved productivity and customer service in the foodand beverage industry by providing customers with an easy ordering platform. Fast foodrestaurants use self-service kiosks to manage the ordering process. When utilizing thistechnology, users may feel more productive and at ease. The researcher aims to determinehow self-ordering kiosks affect customers' convenience and satisfaction and how satisfiedthey make them feel. This method of payment reduces face-to-face interaction,notwithstanding the possibility that the repeated touching of an ordering kiosk couldaccelerate the spread of germs. However, kiosks will require frequent cleaning. Contactlessordering is one way that fast-food joints might stay in business in the near and long term. Self-ordering devices make it simple for consumers to select food by simply glancing at the menusshown on the machine, making them feel more at ease.Data shows that the majority of the respondents are in the age group of 21-25 years old in bothFast food chains, composed of male respondents and are single, while most are self-employed. Customers assess their level of satisfaction in terms of accessibility, location, beingnot familiarized, and having a hard time with troubleshooting. Also, only limited ages areaccessible with it; on the other hand, it is user-friendly. The challenges encountered by theassessment of the two groups and what solution was made by the management: therespondents claim that lagging machines usually stop responding to failed kiosks by some ofthe customers. In the McDonald's situation, software issues may lead to certain featuresbecoming unavailable.Customers should learn how to use the Self-Ordering Kiosks efficiently and properly.Managers must ensure that the available kiosks in their store are working properly and doingtheir job of serving every customer. Moreover, managers must properly train each servicecrew to provide a better quality service to every customer and help them with somedifferences that they experience.
Keywords: Business